Analysis and optimisation of perishable inventory with stocks-sensitive stochastic demand and two-stage pricing: A discrete-event simulation study. Issue 4 (2nd October 2021) - Zhang, Yilin; Lu, Haibing; Zhou, Zhili; Yang, Zhen; Xu, Shengjun
ABSTRACT: This paper studies an important real-life perishable inventory management problem, which has not been properly addressed by the existing research. In the problem setting, a number of agents are renting spaces/shelves from a landlord, the inventory capability of each agent is limited to the rent space, and agents are risk-averse due to their budget. The objective is to maximize the profits of the agents/retailers while minimizing waste and improving customers' shopping experience. To approach the problem, we develop a discrete-event simulation model to determine the optimum inventory scheme for displaying perishables. The proposed simulation model can show sales trajectories with respect to various features and estimate profit curves. Our model improves profits by choosing the right replenishment threshold and price discount. This study has implications to agents/retailers who deal with inventory scheduling and pricing problems for perishables under stochastic conditions.